Implicit Self-Esteem in Borderline Personality and Depersonalization Disorder - Hedrick, Alexis; Berlin, Heather (Frontiers in Psychology, 2012)
Self-identity is disrupted in people with borderline personality disorder (BPD) and depersonalization disorder (DPD), fluctuating with sudden shifts in affect in BPD and experienced as detached in DPD. Measures of implicit self-esteem, free from conscious control and presentation biases, may highlight how such disruptions of self-concept differentially affect these two populations on an unconscious level. We examined implicit self-esteem using the Implicit Association Test, along with measures of emotion, behavior, and temperament, in BPD (n=18), DPD (n=18), and healthy control (n=35) participants. DPD participants had significantly higher implicit self-esteem and were more harm avoidant than BPD and control participants, while BPD participants had more ‘frontal’ behaviors and impulsivity and less self-directedness and cooperativeness than DPD and control participants. Thus, while BPD and DPD commonly overlap in terms of dissociative symptoms and emotional irregularities, differences in self-esteem, behavior, and temperament can help identify where they diverge in terms of their cognition, behavior, and ultimately underlying neurobiology.